BRIDGING THE GAP: EFFECTIVE PARENT COMMUNICATION AND ENGAGEMENT IN DIVERSE EDUCATIONAL SETTINGS - Siddiqui, Munawar (The journal of contemporary issues in business and government, 2024)
This article examines the importance of parent communication and involvement in working with students from diverse-as well as often trauma-impacted immigrant and refugee communities-to foster academic and social development. Using a qualitative research design, the article explores the challenges and opportunities in building relationships between schools and families for immigrant and refugee students by examining the experiences of 10 educators, 10 school administrators and 10 parents from this population. In particular, the research describes the experiences of families who have been displaced from conflict settings, mainly from Afghanistan, and the challenges parents face when interacting with the U.S. public education system. Many parents find it difficult to understand what is expected of them by the U.S. educational system, parents - particularly those who have been detained or displaced - cannot engage with their children's education due to emotional and psychological barriers. The study highlights the need for trauma-informed models such as safe and supportive school environments for children and their families to better meet the unique needs of these populations. In addition, the study uncovered the important role of community-based organizations in mediating between schools and immigrant families by offering vital resources and offering guidance on how to negotiate the educational system. The research also emphasizes the need for empathy-informed practices to address families’ emotional and cultural needs and experiences of conflict zones. “Meeting them halfway” by demonstrating cultural competence and offering frequent, empathetic communication, educators and school leaders can create solid relationships with the immigrant and refugee parents, which will benefit the schooling experiences of school children. This research adds to the relatively small literature on parent engagement in complex school systems throughout diverse education programs, and provides specific ideas for better communicating and supporting immigrant and refugee families within school contexts.